STUDI POWER QUALITY DI BALAI LATIHAN PENDIDIKAN TEKNIK (BLPT) YOGYAKARTA - Alex Sandria Jaya Wardhana (JPTE FT UNY, 2019)
The quality of electrical power is a common condition that describes the characteristics of the parameters of electrical quantities. This study aims to determine the power quality profile that includes current, voltage, active power , reactive power , apparent power, frequency , harmonic current and voltage harmonics. Power quality profile is done by measuring for 24 hours to determine the characteristic qualities of the object of research in Balai Latihan Pendidikan Teknik (BLPT) Yogyakarta. Measurements were taken at each of output transformer 250 kVA at BLPT Yogyakarta . Based on the measurement results , the total peak load for loading in BLPT Yogyakarta is 129.242,45 VA or equal to 51.70% of the installed transformer capacity. The most prominent conditions of measurement results are any indication of the current flow in the neutral wire is high enough, ie 103,05 amperes, which will impact on the value of the energy loss in the neutral wire and losses in the transformer.